OPERATION AND CONTROL OF DIVIDING WALL DISTILLATION COLUMNS Part 1: Degrees of Freedom and Dynamic Simulation - Abdul Mutalib, M I; Smith , R (Institution of Chemical Engineers UK, 1998)
The dividing wall distillation column has been known now for some 50 years. Despite its potential to make major savings in energy and capital costs in distillation, it has not been widely used in practice. One of themajor fears in applying the technologyis uncertainty regarding the control and operation of the arrangement. This paper investigates theoretically the operation and control of the dividing wall column. A degrees of freedom analysis was performed to determine the number of control loops required. Possible control con® gurations were then investigated using Relative Gain Array Analysis and dynamic simulation. The results of these theoretical studies indicate that simple control schemes are capable of providing stable control.